POLYMERASE CHAIN REACTION DETECTION OF AVIAN LEUKOSIS VIRUS DNA IN VACCINES USED IN POULTRY - Acevedo, Ana María; Rodríguez, Edisleidy; Uffo, Odalys; Relova, Damarys; Noda, Julia; Díaz de Arce, Heidy (Revista de Salud Animal, 2014)
Avian leukosis viruses (ALV) provoke a variety of trasmissible bening and malign tumoral diseases affecting birds. Chickens are affected by six subgroups of ALV designs A, B, C, D, E and J of more recent world dissemination. These viruses are potential contaminants of live vaccines used in poultry. In order to research the presence of DNA from ALVs as contaminants of viral commercial vaccines to be used in poultry, different Marek´s disease vaccines were screened by a reported polymerase chain reaction (PCR) assay designed to detect all subgroups of ALVs. DNA samples extracted from seven vaccines were submitted to PCR using primers for a conserved region of env gene of HPRS-103. ALV sequences were detected in seven samples (100%). The methodology employed proved to be useful for the detection of ALVs as contaminants of imported Marek´s disease vaccines. These data suggest a high occurrence of ALVs in commercial vaccines intended for poultry disease prevention.